Rosmarinic Acid Ameliorates Pulmonary Ischemia/Reperfusion Injury by Activating the PI3K/Akt Signaling Pathway - Luo, Wenbin; Tao, Yu; Chen, Shengnan; Luo, Hao; Li, Xiaoping; Qu, Shuang; Chen, Ken; Zeng, Chunyu (Frontiers in Pharmacology, 2022)
Pulmonary ischemia/reperfusion (IR) injury is the leading cause of acute lung injury, which is mainly attributed to reactive oxygen species (ROS) induced cell injuries and apoptosis. Since rosmarinic acid (RA) has been identified as an antioxidant natural ester, this natural compound might protect against pulmonary IR injury. In this study, the mice were given RA daily (50, 75, or 100 mg/kg) by gavage for 7 days before the pulmonary IR injury. We found that hypoxemia, pulmonary edema, and serum inflammation cytokines were aggravated in pulmonary IR injury. RA pretreatment (75 and 100 mg/kg) effectively reversed these parameters, while 50 mg/kg RA pretreatment was less pronounced. Our data also indicated RA pretreatment mitigated the upregulation of pro-oxidant NADPH oxidases (NOX2 and NOX4) and the downregulation of anti-oxidant superoxide dismutases (SOD1 and SOD2) upon IR injury. In vitro studies showed RA preserved the viability of anoxia/reoxygenation (AR)-treated A549 cells (a human lung epithelial cell line), and the results showed the protective effect of RA started at 5 μM concentration, reached its maximum at 15 μM, and gradually decreased at 20-25 μM. Besides, RA pretreatment (15 μM) greatly reduced the lactate dehydrogenase release levels subjected to AR treatment. Moreover, the results of our research revealed that RA eliminated ROS production and reduced alveolar epithelial cell apoptosis through activating the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) signaling pathway, which was supported by using wortmannin, because in the presence of wortmannin, the RA-mediated protection was blocked. Meanwhile, wortmannin also reversed the protective effects of RA in mice. Together, our results demonstrate the beneficial role of RA in pulmonary IR injury via PI3K/Akt-mediated anti-oxidation and anti-apoptosis, which could be a promising therapeutic intervention for pulmonary IR injury.